2011
DOI: 10.1002/sia.3502
|View full text |Cite
|
Sign up to set email alerts
|

Molecular ions in cluster bombardment: what clues do the molecular dynamics simulations provide?

Abstract: Molecular dynamics simulations of C 60 bombardment of molecular solids suggest that there is a space-time divide between the fragmentation/ion creation process and the ejection of intact molecules via fluid flow physics. This space-time divide leads to the conclusion that molecular ions are preformed prior to ejection. Consequently, to increase the ion yield significantly, the sample must be altered to create more preformed ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…This allows D‐rich fragments from the enriched layer to come into contact with PHE molecules in lower layers. This is a process in support of DCPI proposed recently . Alternatively, in the case where the enriched film is on the bottom, the width of the [M PHE + D] + peak is half the size as in the preceding case.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…This allows D‐rich fragments from the enriched layer to come into contact with PHE molecules in lower layers. This is a process in support of DCPI proposed recently . Alternatively, in the case where the enriched film is on the bottom, the width of the [M PHE + D] + peak is half the size as in the preceding case.…”
Section: Resultssupporting
confidence: 76%
“…Thus, the possibility of exchange not due to primary ion impact is negligible. Molecular depth profiling is performed, and exchange of a deuteron from fragmented PHE‐D 8 molecules is observed in the form of the [M PHE + D] + molecule, yielding strong evidence for dynamically created pre‐formed ions (DCPI) …”
Section: Introductionmentioning
confidence: 99%
“…The picture of the energetic collisions in the first hundreds of femtoseconds of the interaction allows us to speculate about the reasons of the observed discrepancy between the sputtering yield and the ion yield enhancements when going from atomic Bi projectiles to clusters. In addition to the possibility of preformed ions, 66,67 it has long been thought, 68,69 and also shown in previous simulation works, 70 that significant ionization occurs in the energetic collision cascade, at the beginning of the interaction. It seems very difficult to explain the aforementioned discrepancy with the concept of preformed ions, because in that case, the sputtering and ion yields should, in principle, be proportional to each other.…”
Section: Resultsmentioning
confidence: 88%
“…A systematic study varying the salt content of the samples would be required to clarify this issue. However, MD studies have shown that preformed protonated ions can be expected to be emitted from the low energy periphery of a high energy primary ion impact site. , It is envisaged that some protons formed during high-energy fragmentation during the initial impact flow out to the periphery and encounter intact molecules. Protonated molecular ions are formed and emitted, possibly during a subsequent primary impact.…”
Section: Resultsmentioning
confidence: 99%